Case Control Study Of The Occurrence Factors Of Low Birth Weight (LBW) In The Dr. SoerotoNgawi Hospital - Pariyem Pariyem (Journal for Quality in Public Health, 2020)
Infant morbidity and mortality (IMR) is an indicator in determining health status. Because the infant mortality rate is able to describe the state of health of both mother and baby including LBW and HIV / AIDS. This Research aimed to knowing the case control study of the occurrence factors of low birth weight (LBW) in the dr. SoerotoNgawi Hospital.Retrospective with case control study design. Research executed on 25 July to 7 August 2019 in Dr. SerotoNgawi Hospital. with population of all postpartum mothers who have babies as many as 2901 and a large sample of cases 176 and 176 control . Data approach used observations by medical record and analyzed with Chi-Square test and binary logistic regression.The Factors Of incidence Low Birth Weight (LBW) in the dr. SoerotoNgawi Hospital. is HIV p-value 0,000; OR = 0.042; HB (p-value 0,000, OR 3,465) and ANC (p-value 0,000, OR 0,14).There is HB level is that factor dominant incidence of Low Birth Weight (LBW) in the dr. SoerotoNgawi Hospital.The hospital's efforts to improve IEC, HIV surveillance and care of LBW risk groups. Action needs to be taken for LBW to maintain body temperature with in incubator, the Kangaroo method and adequate nutrition intake